Experimental Work for Bar Straightness Effect Evaluation of Split Hopkinson Pressure Bar - Afdhal Afdhal; Leonardo Gunawan; Tatacipta Dirgantara (Institute for Research and Community Services, Institut Teknologi Bandung, 2021)
Bar straightness is one of several factors that can affect the quality of the strain wave signal in a Split Hopkinson Pressure Bar (SHPB). Recently, it was found that the bar components of the SHPB at the Lightweight Structures Laboratory displayed a deviation in straightness because of manufacturing limitations. An evaluation was needed to determine whether the strain wave signals produced from this SHPB are acceptable or not. A numerical model was developed to investigate this effect. In this paper, experimental work was performed to evaluate the quality of the signal in the SHPB and to validate the numerical model. Good agreement between the experimental results and the numerical results was obtained for the strain rates and stress-strain relationship for mild steel ST37 and aluminum 6061 specimen materials. The recommended bar straightness tolerance is proposed as 0.36 mm per 100 mm.